2018
DOI: 10.3390/s18020425
|View full text |Cite
|
Sign up to set email alerts
|

Game Theory-Based Cooperation for Underwater Acoustic Sensor Networks: Taxonomy, Review, Research Challenges and Directions

Abstract: Exploring and monitoring the underwater world using underwater sensors is drawing a lot of attention these days. In this field cooperation between acoustic sensor nodes has been a critical problem due to the challenging features such as acoustic channel failure (sound signal), long propagation delay of acoustic signal, limited bandwidth and loss of connectivity. There are several proposed methods to improve cooperation between the nodes by incorporating information/game theory in the node’s cooperation. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 84 publications
(120 reference statements)
0
28
0
Order By: Relevance
“…Each simulation run corresponds to the transmission of a total of six packets from the legitimate transmitter to all trusted nodes, and of one packet from the attacker, also directed to all trusted nodes. Each packet includes 100 symbols, out of which each trusted node produces 100 estimates of the channels' number of taps (3), relative RMS delay spread (6), and the smoothed received power (8), which have been found to offer sufficient diversity to enable our authentication scheme. Since the transmitted signals were wideband (relative to the carrier frequency) and transmitted with high SNR, channel estimates were obtained by processing the received signals through a normalized matched filter.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Each simulation run corresponds to the transmission of a total of six packets from the legitimate transmitter to all trusted nodes, and of one packet from the attacker, also directed to all trusted nodes. Each packet includes 100 symbols, out of which each trusted node produces 100 estimates of the channels' number of taps (3), relative RMS delay spread (6), and the smoothed received power (8), which have been found to offer sufficient diversity to enable our authentication scheme. Since the transmitted signals were wideband (relative to the carrier frequency) and transmitted with high SNR, channel estimates were obtained by processing the received signals through a normalized matched filter.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Successfully forwarding and transferring data between participating sensor nodes in the UASN is an important aspect of reliability. Reliability guarantees successful delivery of packets between sensor nodes participating in collaborative processes [100]. The review of this study found that reliability is the most important aspect, but unfortunately, most of the current studies have not considered.…”
Section: Rssi [70]mentioning
confidence: 93%
“…Efficiency is also a basic aspect in a communication network to provide an efficient cooperative mechanism and to facilitate communication among different nodes. Based on our review of the current algorithms, it has been found that no method takes into account this aspect [100,101]. Collaborative controlling activities require an efficient method for successful data forwarding and delivery in underwater localization.…”
Section: Rssi [70]mentioning
confidence: 99%
“…The projected protocol consists of two parts named as Candidate Node choice part for shrewd Fitness by the causation Node and target node choice phase by the knowledge of routing Table and choose the forwarding node with highest fitness as Target Node [15]. Every of those elements are mentioned during this section.…”
Section: Overview Of Efficient Noise Aware Level Based Routing Protocmentioning
confidence: 99%